Pests of Crops in Warmer Climates and Their Control - Hill, Dennis S. (Springer Netherlands : Imprint: Springer, 2008)
A textbook providing basic data about the crop pests and the damage they inflict throughout the tropics and sub-tropics. Each major pest is illustrated by either a line drawing or a photograph, and sometimes the damage can also be seen. A world distribution map is provided for each species. Control measures tend to be general rather than very specific. Most of the pests are insects and mites, but some nematodes, molluscs, birds and mammals are included.